Tinjauan Literatur tentang Pengaruh Pemupukan Organik terhadap Pertumbuhan dan Hasil Tanaman Jagung (Zea mays L.) - Novita Debora Zega; Julvan Ndruru; Cipria Agus Iman Zalukhu; Edwin Kaskar Jaya Lase; Yoel Melsaro Larosa (CV. SINAR HOWUHOWU, 2026)
Corn (Zea mays L.) is an important food commodity that plays a strategic role in meeting the needs for food, feed, and industrial raw materials. Efforts to increase corn production require support from sustainable soil fertility management, one of which is through the use of organic fertilizers. Organic fertilization is known to improve the physical, chemical, and biological properties of soil, thereby supporting optimal plant growth and development. This article aims to review various research findings regarding the effect of organic fertilization on corn growth and yield. The method used was a literature review, reviewing various scientific journals, books, and relevant academic sources. The results indicate that the application of organic fertilizers, such as manure, compost, and liquid organic fertilizers, generally has a positive effect on corn growth. Organic fertilizer application can increase plant height, leaf number, stem diameter, root development, and corn productivity by increasing nutrient availability and soil microbial activity. Furthermore, the use of organic fertilizers also contributes to increasing soil organic matter content and nutrient use efficiency. Based on the review, it can be concluded that organic fertilization is an effective and environmentally friendly alternative to support corn growth and yield. The combination of organic fertilizer and proper cultivation management has the potential to sustainably increase crop productivity and maintain long-term soil quality.